Phages drive the dissemination of antibiotic resistance genes by facilitating host adaptation to heavy metal stress - Luo-Qin Shen; Lu Wang; Zhiyuan Yao; Da Lin; Yu-Qiu Ye; Wan-rong Zhang; Mao Ye; Ming-Ming Sun; Shuai Du; Di Wu; Patrick O’Connor; Dong Zhu (Proceedings of the National Academy of Sciences, 2026)
Heavy metals are increasingly recognized as major drivers of antibiotic resistance gene (ARG) dissemination in soil ecosystems. However, the role of phages in heavy metal–driven ARG dissemination and the underlying mechanisms remain poorly understood. Here, through integrative metagenomic, viromics, and metabolomic analyses of paddy soils across China, we reveal that soil phages promote ARG dissemination under heavy metal stress, likely through two potential mechanisms. First, phage-encoded auxiliary metabolic genes (AMGs) reprogram host metabolism to enhance bacterial survival and adaptation, thereby facilitating the cotransfer of adjacent ARGs and indirectly promoting horizontal dissemination. Second, phage-encoded heavy metal detoxification genes (HDGs) directly mediate metal detoxification, driving the cotransfer of neighboring ARG fragments and inducing lipid peroxidation–associated increases in membrane permeability, which collectively enhance ARG mobilization. We further identify a significant enrichment of lysogenic phages coharboring ARGs with AMGs or HDGs (AMG–ARG and HDG–ARG fragments), underscoring their contribution to ARG dissemination. Phage transplantation experiments confirm that elevated heavy metal stress triggers lysogenic phage-mediated ARG transduction to bacterial hosts. Cumulatively, our experiments highlight the pivotal role of phages in mediating ARG transfer under heavy metal pressure and underscore the necessity of incorporating phage dynamics into ARG risk assessments.